2020
DOI: 10.35848/1882-0786/abcb49
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of Ga-rich current pathways created in an n-Al0.7Ga0.3N layer grown on an AlN template with dense macrosteps

Abstract: To clarify the behavior of the AlGaN in 20 nm wide Ga-rich current pathways in an n-AlGaN layer, which assists carrier localization in AlGaN-based light-emitting diodes, we performed a detailed analysis using an n-Al0.7Ga0.3N layer on AlN with dense macrosteps on a 1.0° miscut sapphire substrate. Energy-dispersive X-ray spectra, obtained using cross-sectional scanning transmission electron microscopy calibrated by Rutherford backscattering and cross-sectional cathodoluminescence spectra, indicated that AlN mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…It has been reported the AlN molar fraction observed by TEM-EDS possesses a residual error from the value observed by STEM coupled with Rutherford backscattering. 35) Figures 5(a) and 5(b) show cross-sectional SEM images around the exfoliated interface before the LLO and its corresponding CL panchromatic image. Figures 5(c) and 5(d) present the CL intensity maps obtained from the line profiles for lines I and II in Fig.…”
Section: (F)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported the AlN molar fraction observed by TEM-EDS possesses a residual error from the value observed by STEM coupled with Rutherford backscattering. 35) Figures 5(a) and 5(b) show cross-sectional SEM images around the exfoliated interface before the LLO and its corresponding CL panchromatic image. Figures 5(c) and 5(d) present the CL intensity maps obtained from the line profiles for lines I and II in Fig.…”
Section: (F)mentioning
confidence: 99%
“…5(e)] and concave [Fig. 5(f)] regions were estimated to 0.56 and 0.54 with bowing parameters of 1.0, 35) respectively. The AlN molar fraction of u-AlGaN on the convex region [Fig.…”
Section: (F)mentioning
confidence: 99%
“…Our recent analytical studies on AlGaN layers with dense macrosteps revealed the generation of metastable Al n/12 Ga 1−n/12 N (n is an integer from 2 to 10) along macrostep edgelines. Results from our previous works indicated that the atomic configurations of Al n/12 Ga 1−n/12 N should have 2 or fewer monolayer (ML) configurations [31][32][33][34][35][36][37][38]. Hereafter, n ML, represents the periodicity of the structure in the c[0001] direction, where n is the number of atomic layers in a unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13–15 ] A systematic study of this phenomenon by different groups using both technologies revealed a wide range of ordering from a simple bilayer (1:1) period to much longer, up to 12 ML and even 30–40 nm or incommensurate periods. [ 16–20 ] There are several points of view on the physical driving forces of this phenomenon in AlGaN layers.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] A systematic study of this phenomenon by different groups using both technologies revealed a wide range of ordering from a simple bilayer (1:1) period to much longer, up to 12 ML and even 30-40 nm or incommensurate periods. [16][17][18][19][20]…”
mentioning
confidence: 99%